Eye-tracking in recent L2 learner process research: A review of areas, issues, and methodological approaches. (July 2019) - Abdel Latif, Muhammad M.M.
Abstract: Over the last few years, there has been a noticeable increase in the use of eye-tracking in second language (L2) learner process research. The previous reviews of eye-tracking language research have focused primarily either on providing guidelines for using this technological data source and/or on highlighting selected eye-tracking studies in one or two second language acquisition (SLA) areas. Thus, there is still a need for a review that covers the research and methodological issues of using eye-tracking in multiple L2 learner process areas. Addressing such gap, this paper reviews the eye-tracking L2 learner process studies published between 2011 and 2018. Specifically, the paper focuses on reviewing the eye-tracking L2 learner process research areas, the issues addressed by the studies in each area, and the data collection and analysis approaches used in these studies. It was found that eye-tracking has been used in eight L2 learner process research areas: vocabulary processing and learning, listening comprehension, syntactic processing, written text production, reading comprehension, text-based computer-mediated communication (CMC), oral communication, and data validation. The paper reveals that data collection and analysis approaches have differed from one area to another, and it provides some research and methodological suggestions.